The Teaching of Missiology to Young Christian Women - Valentine, Ririn; Indrawan, Yayan (Jurnal Teologi Trinity, 2024)
Christian young women mostly keep marriage, love and motherhood. This happens because the women are lower than the youth. However, Christ exalted women and declared that girls and boys were equal. The author uses an exposition research strategy to discuss the novelty of the work, using books, journal articles as discussion references. The purpose of writing this article is to clarify the position of Christian women and underscore the importance of young people in teaching missiology, namely to show that women can serve in various roles. The findings from the research show that Jesus Christ uplifted young women to Christianity, and that young people also contribute to the spread of missiology through their work in ministry. This shows that in order to get rid of the shackles and mentality of the oppressed young woman, the Christian girl must be brave, devoted, and persistent so as not to weaken.